2021
DOI: 10.1111/aas.13994
|View full text |Cite
|
Sign up to set email alerts
|

Total opioid‐free general anaesthesia can improve postoperative outcomes after surgery, without evidence of adverse effects on patient safety and pain management: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 56 publications
5
39
0
6
Order By: Relevance
“…Another possible source of bias could be the heterogeneous manner of reporting pain score among studies. However, converting the value to a reference scale has been widely validated previously [ 22 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible source of bias could be the heterogeneous manner of reporting pain score among studies. However, converting the value to a reference scale has been widely validated previously [ 22 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 In another meta-analysis, OFA significantly reduced adverse postoperative events with significantly lower postoperative opioid consumption. 11 However, the literature on OFA is still controversial because some studies that have not shown benefits 12 , 13 or worse outcomes. 14 Now, the question is which patients and types of surgery benefit the most from the application of OFA.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, opioids are associated with well-known adverse effects such as ileus, delirium, sleep disturbance [ 28 ], respiratory depression, PONV [ 29 ], hyperalgesia [ 30 ] and the promotion of malignancies [ 31 ]. These recent issues have questioned the perioperative use of opioids, and intraoperative opioid use was therefore challenged by several clinical studies suggesting that opioid-free or opioid-sparing anesthesia may be more effective in providing adequate analgesia and reducing opioid-related adverse effects [ 29 , 32 , 33 ]. To our knowledge, to achieve the opioid-free or opioid-sparing anesthesia, opioids should be avoided during surgery and replaced by another hypnotics or analgesics to deal with surgical stimulations.…”
Section: Discussionmentioning
confidence: 99%